Prolifing Swedish teachers’ knowledge base in probability - Nilsson, Per; Lindström, Torsten (NOMAD Nordic Studies in Mathematics Education, 2013)
This paper aims at profiling Swedish teachers’ knowledge base in probability. 43 teachers in compulsory school answered a questionnaire on probability estimation tasks and concept tasks. In the concept tasks, they were challenged to explain their solutions and the content involved in the probability estimation tasks. We distinguish five patterns in the teachers’ knowledge profile: 1) a basic understanding of the theoretical interpretation of probability, 2) problems with structuring compound events, 3) difficulty with conjunction and conditional probability, 4) a higher degree of common content knowledge than of specialized content knowledge and 5) limited understanding of random variation and principles of experimental probability.